Spiritual Rationality and Social Actions of Pesantren Leaders in the BUMPes Incubation Assistance Program: A Narrative Hermeneutic Study in Ponorogo, East Java, Indonesia - Syahrudin Syahrudin; Ishomuddin Ishomuddin; Oman Sukmana; H.M. Suyudi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to analyze the social actions of pesantren leaders in managing the Incubation Program of Pesantren-Owned Enterprises (BUMPes) and to explain the construction of spiritual rationality underlying decision-making and Islamic social entrepreneurship. A qualitative approach employing a narrative-hermeneutic method based on Max Weber's social action theory was adopted. The research was conducted at Al-Muttaqin Islamic Boarding School, Munggung, Pulung, Ponorogo, East Java. Data were collected through in-depth interviews, participatory observation, focus group discussions, and document analysis. The data were analyzed using Miles and Huberman's interactive analysis model combined with Riessman's narrative interpretation. The findings reveal that pesantren leaders perceive BUMPes not merely as an economic initiative but as an instrument of dakwah, social worship, and community empowerment. Their social actions integrate instrumental, value-oriented, affective, traditional, and spiritual rationalities, forming the Spiritual Rationality of Pesantren (SRP) model. Ethical values such as sincerity (ikhlas), trustworthiness (amanah), cooperation (ta'awun), responsibility, and blessing (barakah) serve as the foundation of institutional governance. The study concludes that spiritual rationality constitutes an essential dimension of Islamic social entrepreneurship and introduces the concept of Spiritual Capital as a theoretical extension of Weber's rationality framework within the context of Islamic institutions.